Analysis of Local Spatial Data Infrastructure to Support Volcanic Mudflow Mitigation along Putih River, Magelang Regency, Central Java Province, Indonesia - Afrinia Lisditya Permatasari; Ika Afianita Suherningtyas; Putu Perdana Kusuma Wiguna (Universitas Muhammadiyah Surakarta, 2020)
One of the most devastating disasters in Indonesia was the Mount Merapi eruption in 2010. After the eruption there still exists the secondary hazard of volcanic mudflow, which has caused damage and casualties. Volcanic mudflow is a mixture of pyroclastic material and rainwater, meaning that in the rainy season the area along rivers becomes a high volcanic mudflow hazard, including the area along Putih River in Magelang Regency, Central Java Province. The development of Spatial Data Infrastructure (SDI) plays an important role in disaster management, especially in disaster mitigation efforts. Building an SDI which shares information on spatial conditions in the area along the Putih River could save many lives and reduce the risk from volcanic mudflow. This research was conducted employing interview surveys, field surveys and secondary data collection at government institutions. The results of the analysis have provided a geoportal prototype as an information gateway for the mitigation of volcanic mudflow along the Putih River and the reduction of disaster risk both for the government and community.